40 years FORM: Some new aspects?. (October 2015) - Breitung, Karl
Abstract: 40 years ago Hasofer and Lind wrote their seminal paper[13] about FORM where they described an algorithm for finding the beta point. This algorithm, later in 1978 generalized by Rackwitz and Fiessler in[23] to include nonnormal random variables, is known as Hasofer-Lind–Rackwitz-Fiessler (HL–RF) algorithm and till now it is an important tool for reliability calculations. Here its relation with standard numerical optimization is explained. Further a simple method for computing the SORM factor is given and the connection of FORM/SORM with dimension reduction concepts is outlined.